Task checklist mobile web application - Mat Noh, Hazril Safarin; Abdul Aziz, Azlan; Abd Rahman, Shukor (College of Computing, Informatics, and Mathematics, 2025)
Managing daily tasks is essential for productivity but can often be perceived as unengaging and lacking a sense of urgency. This project aims to address these issues by developing a gamified task checklist mobile web application. Recognizing that a lack of purposeful engagement and procrastination hinder effective task management, this project aims to provide an enjoyable and motivating alternative to traditional task lists. The project goals were to design a storyboard for a task checklist web application, develop a gamified mobile web application for daily task management, and plan for an evaluation of user engagement with the app. An RAD development approach was adopted. Key gamification elements, such as points, rewards, and achievements, were implemented to enhance user motivation and task completion rates. The test findings indicate that the application has a total engagement value of 92.9% of overall average, which is sufficient proof that the application is truly engaging.